Removal of gastric band does not always lead to significant weight gain - Hanipah, Zubaidah Nor; Punchai, Suriya; Antoine, Heath J.; Brethauer, Stacy A.; Schauer, Philip R.; Aminian, Ali Reza (Mary Ann Liebert, 2020)
Background: Reported outcomes after removal of adjustable gastric band (AGB) are very limited, yet, important to direct patient and surgeon decision-making. The aim of this study was to investigate the medium-term weight changes in patients who underwent AGB removal without an additional bariatric procedure. Methods: In this retrospective study, we analyzed data of 25 patients who had undergone AGB removal without an additional bariatric surgery (2009–2016). Results: The reasons for the AGB removal included gastroesophageal reflux disease (n = 10, 40%), band slippage (n = 5, 20%), band prolapse (n = 5, 20%), band erosion (n = 4, 16%), and planned incisional hernia requiring mesh implantation (n = 1, 4%). At a median follow-up time of 2 years (interquartile range [IQR] 1–4) after laparoscopic AGB removal, the median weight and body mass index changes were +7.3 kg (IQR, −2 and +18) and +1.9 kg/m2 (IQR, −1 and +6), respectively. Forty-eight percent (n = 12) did not gain more than 3 kg of body weight after removal of their gastric band. All patients experienced resolution of their AGB-related symptoms. Conclusion: Recognizing that weight regain is not necessarily inevitable for all patients after gastric band removal may assist in decision-making.